2011
DOI: 10.1007/s11523-011-0202-9
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic toxicities of small molecule tyrosine kinase inhibitors

Abstract: Small molecule tyrosine kinase inhibitors (TKIs) are potent anti-cancer targeted therapies. TKIs are considered safe and efficacious therapeutic modalities, and are generally tolerated well. However, they are associated with certain side effects including hematologic toxicities such as anemia, macrocytosis, neutropenia, thrombocytopenia, hemolytic anemia, bone marrow aplasia and necrosis. Thrombotic microangiopathy, arterial thromboembolism and splenic infarction can also occur following treatment with TKIs. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 73 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Bone marrow analysis, the most invasive test, may be necessary in megaloblastosis, in order to rule out myelodysplastic syndrome. Treatments relying on tyrosine kinase inhibitors (TKIs), such as imatinib, sunitinib, and sorafenib, can now be counted among the possible causes of macrocytosis with previously unexplained pathomechanisms [11, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow analysis, the most invasive test, may be necessary in megaloblastosis, in order to rule out myelodysplastic syndrome. Treatments relying on tyrosine kinase inhibitors (TKIs), such as imatinib, sunitinib, and sorafenib, can now be counted among the possible causes of macrocytosis with previously unexplained pathomechanisms [11, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the increased number of mature megakaryocytes in the bone marrow, inhibition of SFKs results in thrombocytopenia by compromising migration and proplatelet formation. 53,55,62 Our results show that bosutinib and dasatinib were associated more with thrombocytopenia, which is probably due to their mechanism of action against SFKs. Moreover, dasatinib may also affect PDGFRs and their downstream signalling molecules, which contribute to the compromise of platelet activation.…”
Section: Discussionmentioning
confidence: 64%
“…1,54,56,57 In addition to the c-Abl pathway, other avenues that play a key role in normal haematopoiesis are inhibited by TKIs, such as Src, KIT, and platelet-derived growth factor receptor (PDGFR) pathways, which further contributes to myelosuppression. 53,55,58,59 Our analysis shows that cytopenias were typically more frequent with the use of dasatinib in both doses (100 and 140 mg), despite 140 mg not being a usual dose in clinical practice. This drug has a broad spectrum of inhibition of tyrosine kinases (low specificity), including…”
Section: Discussionmentioning
confidence: 83%
“…Myelosuppression may develop at any time during treatment of CML but is common in the initial 2-4 weeks of therapy, especially for advanced disease [21]. Other studies have reported onset of cytopenia between 3 and 5 weeks of imatinib therapy [22]. e development of severe cytopenia rapidly in patients with a myeloid bulge shortly after TKI initiation is a phenomenon that is still under study.…”
Section: Discussionmentioning
confidence: 99%